Democratic Republic of the Congo [In Agricultural Extension] - Ragasa, Catherine; Ulimwengu, John M. (International Food Policy Research Institute, 2020)
This chapter analyzes the provision of agricultural extension and advisory services in the Democratic Republic of the Congo (DRC) in the context of a postconflict country and the experiences and challenges in reconstituting an extension system. Since 1996, the DRC has experienced a succession of wars and lower-scale conflicts that caused more than 5 million deaths over the 1998–2008 period (Maystadt et al. 2014). These have had a devastating effect on the country’s infrastructure, technology, and institutions, creating a vacuum that has led to a laborious process of restoration. As a result, the DRC faces serious food insecurity and human development challenges. In 2011 through 2013 the DRC was ranked as the country with the most severe food insecurity, based on the Global Hunger Index of the International Food Policy Research Institute (IFPRI). It remains so according to current alarming hunger indicators (IFPRI 2016). At least 50 percent of the population is deficient in key nutrients, including iron, vitamin B12, calories, riboflavin, vitamin E, folate, and zinc (Ulimwengu, Roberts, and Randriamamonjy 2012). Life expectancy in the DRC is around 47 years for men and 51 years for women; 1 in 5 children die before reaching age 5 (Pfingu 2011; UNDP 2010).